Pembentukan Public Sphere dalam Game Online - Fadhly Hafizh; Firmansyah; Dadi Ahmadi (UNISBA Press, 2023)
Abstract. Public space is a medium for humans to be able to gather, have recreation, and also open a discussion room. Public space can occur in real life (real space) and in cyberspace (virtual space), this is because public space can be created anywhere, even in the world of online games, public space can be created by the players. One of the online games that has the potential to form a public space is the GTA V Online game, this can happen because in the GTA V Online game the players are connected to an internet network from all over the world and are also assisted by an additional feature, namely the voice chat feature. The purpose of this study is to determine the formation of the public sphere in the game GTA V Online, this study uses a qualitative research method with a case study approach, this research is then assisted by the public sphere theory of Jurgen Habermas. Habermas raises what he calls